Sc(OTf)3 catalyzed [3 + 2]-annulation reaction of donor–acceptor aziridines with methylene exo-glycals: synthesis of chiral carbohydrate-spiro-heterocycles. Issue 10 (10th March 2021) - Zhang, Jie-Hui; Pan, Cheng-Lin; Zhang, Huan-Huan; Xu, Peng-Fei; Luo, Yong-Chun
Abstract : A Sc(OTf)3 catalyzed [3 + 2]-annulation reaction between D–A N -tosyl aziridines and methylene exo -glycals was developed for the synthesis of carbohydrate-spiro-heterocycles. Abstract : A Sc(OTf)3 catalyzed [3 + 2]-annulation reaction between donor–acceptor aziridines and several exo -glycals has been developed. Using this method, some exo -glycals derived from d -ribose, d -galactose and uridine can be converted into carbohydrate-spiro-heterocycles easily in good yields. Simple derivatization of the products gives proline analogues and polycyclic compounds. Moreover, this reaction disclosed the stereochemistry characteristic of the reaction between racemic D–A aziridines and chiral enolethers.